2020
DOI: 10.3390/w12020353
|View full text |Cite
|
Sign up to set email alerts
|

Oblique Wave Attack on Rubble Mound Breakwater Crest Walls of Finite Length

Abstract: Rubble mound breakwaters usually present a crest wall to increase the crest freeboards without a large increase of the consumption of material. Methods in the literature to design crest walls are based on estimates of the wave loads. These methods are focused on the maximum loading that attacks a single position of the crest wall. In practice, crest walls have a finite length. Since the maximum loading does not occur at the same instant over the entire length of the crest wall for oblique waves, these methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…When the wave obliquely enters the elongated structure, the maximum wave force decreases [10,11]. Lately, research results have reported that an increase in wave pressure caused by the diffracted wave can be one of the reasons for destruction of the conventional caisson breakwater [12].…”
Section: Introductionmentioning
confidence: 99%
“…When the wave obliquely enters the elongated structure, the maximum wave force decreases [10,11]. Lately, research results have reported that an increase in wave pressure caused by the diffracted wave can be one of the reasons for destruction of the conventional caisson breakwater [12].…”
Section: Introductionmentioning
confidence: 99%
“…Among the various methods used to produce breakwaters, the elongation of the harbor structure has recently received considerable attention. As shown in Figure 1, the maximum wave force acting on the breakwater can be reduced through consideration of the phase difference of the hydrodynamic pressures by elongating the harbor structure when an oblique incident wave approaches the breakwater, thereby improving the stability of the breakwater [6][7][8][9][10]. Takahashi and Shimosako [8] and Burcharth and Liu [9] analytically showed that the maximum wave force decreases when the wave obliquely enters the elongated structure.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure the safety of the harbor from such environmental changes, it is necessary to maintain the stability of the main breakwater installed at the harbor mouth to prevent waves propagating from the open sea to the harbor. Various studies have been conducted to respond effectively to wave overtopping by increasing the design wave height [7][8][9][10] and utilizing the wave energy corresponding to wave overtopping [11].…”
Section: Introductionmentioning
confidence: 99%